Lasykar Syiah Hudan Constribution in Business Distribution of Islam in XIII Masehi Century Aceh - Usman Ibrahim; Bachtiar Akob; Imam Hadi Sutrisno (Budapest International Research and Critics University, 2020)
Lasykar Syiah Hudan is part of the Zawiyah Cot Kala College, the oldest in Aceh and Southeast Asia, built in the era of the sixth Sultan Peureulak Muhammad Amin Syah Johan Sovereign,early X century AD. One of the great scholars / teachers is Chik Abdullah Kan'an. Center for training activities in Aramiyah / Bayeun (present-day East Aceh). Besides being a professor, Chik Abdullah Kan'an was an adult who was also the leader of Wazirul Harb, the Shia Hudan army in Bandar Khalifah, known as